Pemphigus Herpetiformis in Childhood: Clinical Case - Nikolay N. Murashkin; Alexander I. Materikin; Roman V. Epishev; Maria A. Leonova; Leonid A. Opryatin; Dmitri V. Fedorov; Roman A. Ivanov; Alena A. Savelova; Oksana R. Katunina; Kirill A. Kulikov; Ilgiz I. Yarullin ("Paediatrician" Publishers LLC, 2023)
Background. Pemphigus herpetiformis is a rare atypical bullous dermatosis of autoimmune nature. It is characterized by rashes in the form of plaques with papules and vesicles at peripheral areas, or in the form of grouped papules, vesicles or tense bubbles with clinical similarity to During's herpetiformis dermatitis. Pemphigus herpetiformis diagnosis in pediatric practice is difficult due to the similarity of clinical manifestations to bullous dermatoses of other etiology, the rarity of the disease in children, and small number of scientific publications.Clinical case description. Clinical case of pemphigus herpetiformis in a child is described. All necessary diagnostic algorithms for diagnosis and therapeutic tactics for patient management are presented. Dapsone and prednisolone were used as first-line drugs during the patient's treatment. They have shown its efficacy in management of such patients.Conclusion. Differential diagnosis of pemphigus herpetiformis and other bullous dermatoses in children is presented. The results of successful drug treatment are shown.